IDENTITAS VISUAL DESA WISATA BATIK COKROKEMBANG MELALUI ENVIRONMENT GRAPHIC DESIGN SEBAGAI PENGEMBANGAN DI KABUPATEN PACITAN - Prilosadoso, Basnendar Herry; Suyanto, S.,; Rosmiati, Ana; Handriyotopo, H., (Acintya, 2017)
Moral value awareness had begun to be shifted by the western culture that tended to be incompatiblewith the condition of our society. This research was an effort to give reinforcement of local wisdomcontained in wayang beber figure, as a source for the development of batik patterns of Pacitan. Thegeographical condition of Pacitan Regency was very potential to be developed as a superior ecotourismwhere Pacitan got the nickname as Word class karst geopark tourism area. The economic condition ofthe community was mostly supported by a variety of small and medium industries. Batik industrydeveloped rapidly and had great potential to be developed and improved from the aspect of productivity, so that later could increase the economic level of Pacitan society. This research used actionresearch theory where there were four stages, namely select a focus, collect data, analyze and interpret data, and take action. Methods performed in several stages: assessment, design, socialization,mentoring and training, production, and launching. The research results aimed to increase batikproductivity and creativity through the development of Cokrokembang batik tourism village, Ngadirejo,Pacitan through corporate identity design, so it was expected to increase the economy of the peopleand the opening of the leading tourist attraction in Pacitan.Keywords: local wisdom, corporate identity,, batik tourism.